EDUKASI JALAN KAKI 30 MENIT PADA PASIEN HIPERTENSI - Jundapri, Kipa; Bayudianto, Edy; Suharto, Suharto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Hypertension treatment involves not only pharmacological but also non-pharmacological treatment. Non-pharmacological treatment is 30-minute walk excercise. This community service program aims to educate hypertension sufferers about the importance of regular 30-minute walks to prevent complications and improve their quality of life. The PKM program involved 30 participants, conducted in three stages: pre-education, education, and post-education. The results showed: 65% increase in knowledge, systolic blood pressure decrease 20 mmHg, diastolic blood pressure decrease 10 mmHg, and heart rate decrese 22 kali/menit . Conclusion: walking at least three times a week can lower blood pressure and heart rate within normal limits.